2015
DOI: 10.1002/cvj.12016
|View full text |Cite
|
Sign up to set email alerts
|

Center, Light, and Sound: The Psychological Benefits of Three Distinct Meditative Practices

Abstract: Meditation has been a popular topic in counseling and psychological research in recent years. However, other meditative practices have been gaining exposure recently of which counselors may not be aware. The current article provides a brief overview of 3 meditative practices: centering prayer, jyoti meditation, and acem meditation. The purpose of this article is to provide counselors with introductions to alternative meditative practices that may be otherwise overshadowed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…An advantage is that the method is simple without involvement outside meditation, whereas other techniques may involve some time for training in daily life outside meditation. An overview of different meditation techniques, including Acem Meditation, concluded that an exploration of effects using self-report questionnaires is warranted, as a supplement to fMRI studies (Gutierrez, Fox, & Wood, 2015). The present study is a contribution.…”
Section: Introductionmentioning
confidence: 76%
“…An advantage is that the method is simple without involvement outside meditation, whereas other techniques may involve some time for training in daily life outside meditation. An overview of different meditation techniques, including Acem Meditation, concluded that an exploration of effects using self-report questionnaires is warranted, as a supplement to fMRI studies (Gutierrez, Fox, & Wood, 2015). The present study is a contribution.…”
Section: Introductionmentioning
confidence: 76%
“…It is important to explore how the effects of centering meditation differ or align with meditations in its categories. The literature has three common categories: devotional, focused, or mindfulness meditations (Gutierrez et al, 2015 ). Centering is in a way both devotional and focused.…”
Section: Discussionmentioning
confidence: 99%
“…It is of interest that participants described experiencing spiritual benefits to practicing meditation. The spiritual and cultural aspects of meditation often go unexplored in research (see Gutierrez et al, ; Walsh & Shapiro, ). However, the majority of participants in our study described meditation as helping them to develop a sense of spiritual fulfillment and a deeper connection to the sacred, noting that the spiritual aspects of their experience were important to them.…”
Section: Discussionmentioning
confidence: 99%
“…JM was selected as an appropriate meditation practice to analyze in this study because of the experimental research demonstrating its effectiveness with counselors and because it was a unique practice to which none of the participants had previously been exposed. Additionally, we believe it is important that the counseling literature expand its focus on meditation and include practices that might be more culturally appropriate for various populations (see Gutierrez, Fox, & Wood, ). JM fits this criterion because it does not specify a specific religious orientation but allows the meditator to identify a word or phrase or mantra consistent with the individual's own worldview.…”
Section: Methodsmentioning
confidence: 99%